STUDENT’S MOTIVATIONS IN A PEER-ASSISTED CLINICAL SKILLS TRAINING PROGRAM - Oktadoni Saputra; Doni Widyandana; Tridjoko Hadianto (Fakultas Kedokteran Universitas Lampung, 2014)
Background: Peer-Assisted Learning (PAL) has been widely used in the clinical skills training in medical education. The study of this area shows that PAL-scheme program has benefits both in student tutors and tutees in mastering their clinical skills. However, student’s motivations in this PAL-scheme program haven’t much been explored. The aim of this study is to explore student’s motivations in a peer-assisted clinical skills training program.Method: This study used exploratory focus group discussion (FGD) of 4 groups of 3rd year students (2 tutors and 2 tutees) Faculty of Medicine, Universitas Gadjah Mada and in-depth interview to 6 faculty staffs which were chosen purposively. The data were then transcribed and analyzed for themes.Result: The results of this study showed that when joining a PAL-scheme program, tutees were motivated extrinsically as a preparation for the end of year Objective Structured Clinical Examination (OSCE), whereas tutors were motivated more intrinsically. Various spectrums of motivations were founds, student’s motivations in a peer-assisted clinical skills training program were different between tutors and tutees. Tutors were motivated intrinsically whereas tutees extrinsically.Conclusion: Improvements in organizing PAL program need to be done to enhance the tutees motivation more intrinsically and also to improve the quality and quantity of clinical skills training. [JuKe Unila 2014; 4(8):194-201] Keywords: clinical skills training, internal motivation, motivations, peer-assisted learning, skills-acquisition